2020
DOI: 10.1109/access.2020.2972589
|View full text |Cite
|
Sign up to set email alerts
|

Coding Biological Current Source With Pulsed Ultrasound for Acoustoelectric Brain Imaging: Application to Vivo Rat Brain

Abstract: Conventional noninvasive electroencephalogram (EEG) is limited to poor spatial resolution due to volume conduction effect. To overcome this limitation, the acoustoelectric effect (AE) based acoustoelectric brain imaging (ABI) is proposed for mapping brain electrical activity in a high temporal and spatial resolution. Through phantom and vivo rat brain experiments, this study investigated a biological current source coding mechanism with pulse focused ultrasound (PFU) at pulse repetition frequency (PRF). First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This encoding mechanism was further validated in vivo rat experiments with different PRFs including 500 Hz, 1 kHz, and 2 kHz. Both the AE signal envelope and the decoded AE signal showed a significant correlation with low-frequency EEG (Zhou et al, 2020b ). Next, Zhou evaluated and validated multi-source ABI with different current source functions.…”
Section: Research Progressmentioning
confidence: 99%
“…This encoding mechanism was further validated in vivo rat experiments with different PRFs including 500 Hz, 1 kHz, and 2 kHz. Both the AE signal envelope and the decoded AE signal showed a significant correlation with low-frequency EEG (Zhou et al, 2020b ). Next, Zhou evaluated and validated multi-source ABI with different current source functions.…”
Section: Research Progressmentioning
confidence: 99%
“…In the research of ABI, the Decoding Algorithm with Envelope is frequently utilized (Qin et al, 2012;Qin et al, 2015;Berthon et al, 2017;Preston et al, 2018;Berthon et al, 2019;Zhou et al, 2020;Zhou et al, 2021). The theory (Zhou et al, 2019) stipulates that the AE signal is first converted into an analytical signal.…”
Section: Decoding Algorithm With Envelopementioning
confidence: 99%
“…The basic work of early AE imaging decoded with envelope algorithm (Song et al, 2019;Zhou et al, 2019). Zhou et al, in 2020, conducted the first multi-source acoustoelectric imaging experiment (Zhou et al, 2020), which adopted algorithm based on the envelope function to decode the AE signal. For the first time, ABI decoded the Steady state visual evoked signal in the brain of a living mouse and also exploited the envelope algorithm to decode the AE signal (Song et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately following, Barragan et al used an ex vivo human skull to localize time-varying monopoles and dipoles (two platinum electrodes spaced 10 mm apart) that simulate epileptic discharges at depths greater than 60 mm with a spatial resolution of 1-4 mm [16]. In the same year, Song et al demonstrated the source signal modulation mechanism of pulse repetition frequency (PRF) of FUS by saline and rat brain experiments [17], and the results showed that decoding EEG signals from the modulated AE signals is feasible [18]. In addition, the feasibility of AE effect-based localization of physiological discharge sources in living organisms such as the heart of living rabbits [19,20] and the brain of living rats [21] has been verified in previous studies.…”
Section: Introductionmentioning
confidence: 99%